The fungi recorded in imported feed samples with reference to control of T-2 toxicosis by antioxidant substances in chicks - Mansour, Mogda K.; Hassan, A. A.; Rashid, M. A. (2002)
Fifty samples of imported animal feed were evaluated for fungi and their toxins contamination. Nine genera and eight species of mould were isolated. The genus Mucor and Penicillium (66% and 65%) were predominantly isolated, followed by Aspergillus ( 40% ), Fusarium (20%) and Cladosporium (14%). Belonging to genus Aspergillus, A. flavus was frequently isolated (28%) but F. graminearium was obtained only from 10% of samples. Species of Rhizopus, Scopulariopsis and Alternaria were yielded from 4, 2 and 2% of samples respectively. Tb2(B-toxin (member of trichothecene) was detected in 30% of these samples with the mean amount of 60 ppb and aflatoxin in 20% with the mean amount of 3,4 ppb, whereas ochratoxin A was gained from 14% of samples with mean level of 2.2 ppb, but Zearalenon and Fumonisin B1 toxins were found in 6 and 2% with mean level of 22 and 70 ppb respectively.s
Includes references.
Summary in Arabic.
1
Keywords: Chicks -- Feeding and feeds -- Contamination; Mycotoxicoses in animals; Antioxidants; T-2 toxin